2012
DOI: 10.1093/jscr/2012.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma in middle ear of an adult: a rare presentation

Abstract: Rhabdomyosarcoma of the middle ear is a rare tumor, even rarer in adults and has a very poor prognosis. We report here an unusual case of rhabdomyosarcoma in middle ear of an adult, mimicking chronic suppurative otitis media and facial nerve palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Studies have suggested that distinct genetic factors are involved in the development and tumour progression of RMS, such as loss of heterozygosity, specific chromosomal translocations, and abnormal gene alterations. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that distinct genetic factors are involved in the development and tumour progression of RMS, such as loss of heterozygosity, specific chromosomal translocations, and abnormal gene alterations. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Immunohistochemistry is required to differentially diagnose it from other small round cell neoplasms, namely lymphoma (CD20, CD3 positive) and Ewing's sarcoma/primitive neuroectodermal tumour (CD99 positive) as RMS is negative for these markers. [ 9 ] The RMS tumour cells express Desmin, Myogenin, CD56, muscle-specific actin, Myoglobin, Vimentin, and MyoD1. The demonstration of foetal haemoglobin in tumour tissue by immunoperoxidase staining has been shown to be reliably accurate in identifying RMS.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue stains help differentiate RMS from other tumors with similar histopathology, such as lymphomas (CD20+ and CD3 +), and Ewing's Sarcoma (CD 99+). [10] RMS will be positive for multiple muscle markers, the most specific and sensitive marker is the muscle transcription factors MyoD and Myogenin. [11] The standard of treatment for RMS includes excisional surgery, multidrug chemotherapy, and EBRT.…”
Section: Discussionmentioning
confidence: 99%